A comprehensive review of palliative care in patients with cancer. (February 2014) - Jaiswal, Reena; Alici, Yesne; Breitbart, William
Abstract One of the most challenging roles for the psychiatrist is to help guide terminally ill patients physically, psychologically and spiritually through the dying process. Patients with advanced cancer, and other life-threatening medical illnesses are at increased risk for developing major psychiatric complications and have an enormous burden of both physical as well as psychological symptoms. In fact, surveys suggest that psychological symptoms such as depression, anxiety, and hopelessness are as frequent, if not more so, than pain and other physical symptoms in palliative care settings. Psychiatrists have a unique role and opportunity to offer competent and compassionate palliative care to those with life-threatening illness. In this article we provide a comprehensive review of basic concepts and definitions of palliative care and the experience of dying, and the role of the psychiatrist in palliative care including assessment and management of common psychiatric disorders in the terminally ill, with an emphasis on suicide and desire for hastened death. Psychotherapies developed for use in palliative care settings, and management of grief and bereavement are also reviewed.